2012
DOI: 10.1016/j.electacta.2012.02.099
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of cerium nitrate on AA2024-T3 by means of electrochemical micro-cell technique

Abstract: t r a c tThis work evaluates the effect of cerium nitrate as corrosion inhibitor for AA2024-T3 in the view of its introduction in sol-gel coatings able to provide self-healing ability. Since it is well established that deposition of Ce species is activated by the local pH increase, the objective of this paper is to investigate the behavior of AA2024-T3 (open circuit potential and polarization curves) in the presence of Ce species in aggressive solutions by means of a local technique, the electrochemical micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 37 publications
2
31
0
2
Order By: Relevance
“…Deposition and corrosion properties of CeCC have been studied not only on aluminum alloys but also on other such as magnesium alloys [5][6][7][8] and steel [9][10][11][12] . Most of the research on CeCC on aluminum alloys has been widely focused on protection of high strength alloys with aerospace applications such as AA2024 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and AA7075 20,[33][34][35][36][37][38][39][40] . Other studies include AA5083 12,[41][42][43] , AA6061 [44][45][46] , AA6063 47,48 and AA6082 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Deposition and corrosion properties of CeCC have been studied not only on aluminum alloys but also on other such as magnesium alloys [5][6][7][8] and steel [9][10][11][12] . Most of the research on CeCC on aluminum alloys has been widely focused on protection of high strength alloys with aerospace applications such as AA2024 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and AA7075 20,[33][34][35][36][37][38][39][40] . Other studies include AA5083 12,[41][42][43] , AA6061 [44][45][46] , AA6063 47,48 and AA6082 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial studies by Hinton et al on AA7075-T6 in chloride solution containing CeCl 3 , [11][12][13] the majority of studies have been on AA2024-T3 [16][17][18][19][20][21][22][23][24][25][26] or other alloys like AA5052, 15 AA5083, [27][28][29] series AA6xxx, [30][31][32][33] AA8090 34 and Al metal. 35 The focus has been on the mechanism of inhibition, mainly by CeCl 3 15,17,18,20,21,26-29,35,36 and Ce(NO 3 ) 3 16,19,22,25,37 which both act as efficient inhibitors on aluminium alloys.…”
mentioning
confidence: 99%
“…Environmentally-friendly alternatives to CrCC have been investigated as potential replacements and include rare earth inhibitors and coatings, and sol-gel, among others [20][21][22] . It has been reported that (salts with) rare-earth ions such as Ce, La, Pr, Nd, and Y used as adhesion promoters and provided suitable resistance to corrosion through the formation of insoluble hydroxide/oxide layers [23][24][25][26][27][28] . Because of their low toxicity, rare-earth salts are not considered as health hazard materials.…”
Section: Introductionmentioning
confidence: 99%